2016
DOI: 10.1016/j.jpsychires.2016.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Acute Suicidal Affective Disturbance (ASAD): A confirmatory factor analysis with 1442 psychiatric inpatients

Abstract: Acute Suicidal Affective Disturbance (ASAD) is a newly proposed diagnostic entity that characterizes rapid onset suicidal intent. This study aims to confirm the factor structure of ASAD among psychiatric inpatients, and to determine the clinical utility of ASAD in predicting suicide attempt status. Overall, 1442 psychiatric inpatients completed a battery of self-report questionnaires assessing symptoms theorized to comprise the ASAD construct. Utilizing these data, a confirmatory factor analysis with a one-fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0
7

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 46 publications
3
33
0
7
Order By: Relevance
“…Prior research has shown that effectiveness of universal suicide prevention is limited (e.g., improving help‐seeking behavior in suicide prevention efforts; Klimes‐Dougan, Klingbeil, & Meller, ), and coupled with limited resources, it is essential for universities to strategically identify subsets of high‐risk students and offer indicated prevention services. Our findings suggest that students reporting high comorbidity may be at elevated risk of SA, which is consistent with prior research (Nock et al, ) and highlights a specific role for (hypo)mania and generalized anxiety disorder in predicting SA, which is in line with recent theories on the importance of affective disturbance and overarousal (including core features such as insomnia and irritability) in predicting suicidal intent (particularly when combined with feelings of alienation or helplessness; Stanley, Rufino, Rogers, Ellis, & Joiner, ). More broadly, the results underscore that relatively low‐cost web‐based screening tools may be effective in reaching high‐risk students in need of help (Mortier et al, ) and, if integrated with prevention and intervention services, may reduce the incidence of STB on college campuses.…”
Section: Discussionsupporting
confidence: 91%
“…Prior research has shown that effectiveness of universal suicide prevention is limited (e.g., improving help‐seeking behavior in suicide prevention efforts; Klimes‐Dougan, Klingbeil, & Meller, ), and coupled with limited resources, it is essential for universities to strategically identify subsets of high‐risk students and offer indicated prevention services. Our findings suggest that students reporting high comorbidity may be at elevated risk of SA, which is consistent with prior research (Nock et al, ) and highlights a specific role for (hypo)mania and generalized anxiety disorder in predicting SA, which is in line with recent theories on the importance of affective disturbance and overarousal (including core features such as insomnia and irritability) in predicting suicidal intent (particularly when combined with feelings of alienation or helplessness; Stanley, Rufino, Rogers, Ellis, & Joiner, ). More broadly, the results underscore that relatively low‐cost web‐based screening tools may be effective in reaching high‐risk students in need of help (Mortier et al, ) and, if integrated with prevention and intervention services, may reduce the incidence of STB on college campuses.…”
Section: Discussionsupporting
confidence: 91%
“…However, measures of anhedonia have not yet been incorporated into the measures aimed at assessing these syndromes Stanley, Rufino, Rogers, Ellis, & Joiner, 2016;Tucker, Michaels, Rogers, Wingate, & Joiner, 2016;Yaseen et al, 2010;Yaseen et al, 2014;Yaseen, Gilmer, Modi, Cohen, & Galynker, 2012). Our findings suggest that measures targeting acute anhedonia, such as the SLIPS , could be an important addition to the assessment of these syndromes.…”
Section: Discussionmentioning
confidence: 92%
“…These proposed syndromes posit severe affective disturbance combined with physiological arousal and varying degrees of cognitive disturbance as syndromal states driving a transition to suicidal action. However, measures of anhedonia have not yet been incorporated into the measures aimed at assessing these syndromes (Galynker et al., ; Hawes, Yaseen, Briggs, & Galynker, ; Rogers et al., ; Stanley, Rufino, Rogers, Ellis, & Joiner, ; Tucker, Michaels, Rogers, Wingate, & Joiner, ; Yaseen et al., ; Yaseen et al., ; Yaseen, Gilmer, Modi, Cohen, & Galynker, ). Our findings suggest that measures targeting acute anhedonia, such as the SLIPS (Winer et al., ), could be an important addition to the assessment of these syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…Two candidate acute suicide‐specific diagnosable conditions have been proposed and supported by preliminary research: the suicide crisis syndrome (SCS; Galynker et al., ; Yaseen, Gilmer, Modi, Cohen, & Galynker, ; Yaseen et al., , ) and acute suicidal affective disturbance (ASAD; Rogers, Chiurliza, et al., ; Rogers, Galynker, Yaseen, DeFazio, & Joiner, ; Stanley, Rufino, Rogers, Ellis, & Joiner, ; Tucker, Michaels, Rogers, Wingate, & Joiner, ).…”
mentioning
confidence: 99%